ORGANIZATION OF AN ACCOUNTING PROGRAM. - Fertig, Paul E. (The Accounting Review, 1960)
Abstract The article focuses on the organization of an accounting program in the U.S. According to the author, the accountant of the future, because of his specialty in quantitative controls, will be expected to have a more thorough grounding in numerical analysis, mathematical statistics, and courses involving operations-research, than perhaps any of the other specialties in the management group. He must have an educational background which is as broad as the background of prospective manager. Any steps which have the effect of pulling accounting education away from the business framework in which it has its origin, are steps in the wrong direction. the "ideal" educational program for professional accountants, would consist of an undergraduate program in the liberal arts, a two-year program in business, followed by whatever professional accounting work might be considered appropriate for the university to offer. Additional work in accounting at the professional level is a long-run problem which should be the joint responsibility of university accounting faculties and professional development programs.